2018
DOI: 10.1007/s00299-018-2251-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous site-directed mutagenesis of duplicated loci in soybean using a single guide RNA

Abstract: Using a gRNA and Agrobacterium-mediated transformation, we performed simultaneous site-directed mutagenesis of two GmPPD loci in soybean. Mutations in GmPPD loci were confirmed in at least 33% of T seeds. The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated endonuclease 9 (Cas9) system is a powerful tool for site-directed mutagenesis in crops. Using a single guide RNA (gRNA) and Agrobacterium-mediated transformation, we performed simultaneous site-directed mutagenesis of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 30 publications
3
65
1
1
Order By: Relevance
“…Multiplex mutations have been induced by CRISPR‐Cas9 in several crops, such as hexaploid wheat (Gil‐Humanes et al ., ; SĂĄnchez‐LeĂłn et al ., ), paleopolyploid maize (Char et al ., ) and allotetraploid rapeseed (Li et al ., ). In soya bean, the CRISPR‐Cas9 system has been successfully utilized to create nonheritable somatic mutations in hairy root cultures and/or whole‐plant heritable mutations (Cai et al ., , ,b; Curtin et al ., ; Du et al ., ; Jacobs et al ., ; Kanazashi et al ., ; Li et al ., ; Michno et al ., ; Sun et al ., ). It has been repeatedly shown that a single sgRNA can induce simultaneous mutations on endogenous genes in soya bean (Du et al ., ; Jacobs et al ., ; Kanazashi et al ., ; Sun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex mutations have been induced by CRISPR‐Cas9 in several crops, such as hexaploid wheat (Gil‐Humanes et al ., ; SĂĄnchez‐LeĂłn et al ., ), paleopolyploid maize (Char et al ., ) and allotetraploid rapeseed (Li et al ., ). In soya bean, the CRISPR‐Cas9 system has been successfully utilized to create nonheritable somatic mutations in hairy root cultures and/or whole‐plant heritable mutations (Cai et al ., , ,b; Curtin et al ., ; Du et al ., ; Jacobs et al ., ; Kanazashi et al ., ; Li et al ., ; Michno et al ., ; Sun et al ., ). It has been repeatedly shown that a single sgRNA can induce simultaneous mutations on endogenous genes in soya bean (Du et al ., ; Jacobs et al ., ; Kanazashi et al ., ; Sun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In multiple eudicot species that belong to the rosid order of Fabales, orthologs of the KIX and PPD proteins have been reported to negatively regulate seed pod size (Ge et al, 2016;Kanazashi et al, 2018;Li et al, 2019;Naito et al, 2017). To examine whether the KIX proteins might also have a role in determining tomato fruit size in the asterid model species tomato, we investigated whether the development of reproductive organs was affected in tomato kix8 kix9 mutants.…”
Section: Tomato Kix8 Kix9 Mutants Produce Bigger Tomato Fruitsmentioning
confidence: 99%
“…In Arabidopsis, the asymmetric cell division of meristemoids, which are precursor cells of the stomatal lineage, positively affects final leaf size and is restricted by a transcriptional repressor complex in which the co-repressor TPL is recruited to PPD2 by KIX8/KIX9 (Gonzalez et al, 2015;White, 2006). Members of this repressor complex were shown to regulate leaf size and shape in a variety of species that belong to different orders of the rosids (Ge et al, 2016;Gonzalez et al, 2015;Kanazashi et al, 2018;Li et al, 2019;Naito et al, 2017), suggesting that the repressor complex is a conserved regulator of leaf growth among rosid eudicots. Here, we demonstrate that the tomato orthologs of KIX8 and KIX9 act as TPL adaptors for PPD proteins as well and, thereby, regulate leaf growth in tomato, a model species of the asterid clade that also includes tobacco (Nicotiana tabacum), carrot (Daucus carota) and sunflower (Helianthus annuus).…”
Section: Kix8 and Kix9 Are Conserved Regulators Of Leaf Growth In Dismentioning
confidence: 99%
See 1 more Smart Citation
“…A protocol for whole plant transformation has been well documented (Liu et al 2019). Successful stable lines have been generated to disable the GmFT2a family, the GmSPL9 family, and two copies of PEAPOD genes to alter flowering time, root nodule number, and seed pod morphology, respectively (Bao et al 2019;Cai et al 2018aCai et al , 2019Kanazashi et al 2018). Nonetheless, the generation of stably edited lines largely relies on the soybean transformation efficiency, editing efficiency, and inheritability.…”
Section: Recent Development In Soybean Breeding Technologiesmentioning
confidence: 99%